2018
DOI: 10.1016/j.jweia.2018.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic performance of a horizontal axis wind turbine with forward and backward swept blades

Abstract: Blades are the most important components of wind turbines in order to convert wind energy to mechanical energy. This study investigates the aerodynamic performance of Horizontal Axis Wind Turbines (HAWTs) with forward and backward swept blades. The effect of the blade sweep direction, the location of the sweep start up and the tip offset on the aerodynamic performance are investigated using a model HAWT with a 0.9 m rotor as the baseline configuration. Changes in power and thrust coefficients with swept blades… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 16 publications
0
24
1
1
Order By: Relevance
“…[14], Turbin angin jenis HAWT dan VAWT, mempunyai kelebihan dan kekurangan yang tergantung pada kecepatan angin dan tempatnya.Turbin angin sumbu horizontal dengan bilah baling-baling adalah yang paling umum, karena efisiensinya sekitar 60%. [8],turbin angin memiliki dinamika nonlinear, kekuatan penggerak stokastik dan tidak terkendali sebagai input dalam bentuk kecepatan angin, Metode kontrol yang sesuai dapat memberikan optimisasi berkelanjutan [13] Dengan menaikkan batas kecepatan flutter yang mengontrol gerakan aileron dengan fuzzy logic. Dengan menganalisis kecepatan flutter menggunakan metode-p, maka dapat diketahui batas kecepatan flutter, dan dengan control LQG dan fuzzy logic maka fenomena flutter dapat teratasi [2], model sistem pembangkit listrik dengan sel surya untuk rumah menggunakan panel jenis polikristalin mampu bekerja maksimum pada pukul 10.00 hingga 13.00 wib pada tegangan 17,5 volt [11]…”
Section: Dalam Skala Global Berdasarkan Data Dariunclassified
“…[14], Turbin angin jenis HAWT dan VAWT, mempunyai kelebihan dan kekurangan yang tergantung pada kecepatan angin dan tempatnya.Turbin angin sumbu horizontal dengan bilah baling-baling adalah yang paling umum, karena efisiensinya sekitar 60%. [8],turbin angin memiliki dinamika nonlinear, kekuatan penggerak stokastik dan tidak terkendali sebagai input dalam bentuk kecepatan angin, Metode kontrol yang sesuai dapat memberikan optimisasi berkelanjutan [13] Dengan menaikkan batas kecepatan flutter yang mengontrol gerakan aileron dengan fuzzy logic. Dengan menganalisis kecepatan flutter menggunakan metode-p, maka dapat diketahui batas kecepatan flutter, dan dengan control LQG dan fuzzy logic maka fenomena flutter dapat teratasi [2], model sistem pembangkit listrik dengan sel surya untuk rumah menggunakan panel jenis polikristalin mampu bekerja maksimum pada pukul 10.00 hingga 13.00 wib pada tegangan 17,5 volt [11]…”
Section: Dalam Skala Global Berdasarkan Data Dariunclassified
“…Meanwhile, it has better aerodynamic performance than the straight blade and the fore-swept blade. Kaya et al [27] investigated the aerodynamic performance of Horizontal Axis Wind Turbines (HAWTs) with forward and backward-swept blades and found that the forward-swept blades can increase the performance while the backwardswept blades tend to decrease the thrust coefficient. To model and analyze the effect of the circumferential nonuniformity on the flow field of a swept cascade, a kind of stress transport model was integrated into the throughflow model by 3D numerical simulation.…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
“…Vad et al (2015) comprehensively described the characteristics of forward-swept blades. Combining straight blades and forward-swept blades can increase the efficiency of the fan by 2-3%, although for free-vortex rotors, there is little improvement in efficiency (He et al, 2018;Kaya et al, 2018).…”
Section: Introductionmentioning
confidence: 99%